Determination of the Properties of Medium-Density Fiberboards Produced Using Urea-Formaldehyde Resins Modified with Boron Compounds - Recai Arslan; Ebru Karaçay; Derya Maraşlıoğlu; Bilge Aslan Tanrıverdi; Ebru Fırat; Ayhan Tozluoğlu; Halil İbrahim Uğraş; Zeki Candan (BioResources)
Effects of adding different boron compounds to the urea-formaldehyde resin were evaluated relative to the physical, mechanical, and other properties of medium-density fiberboard (MDF). While the chemical addition of boric acid to the urea-formaldehyde resin increased the modulus of rupture and modulus of elasticity values of MDF boards, the physical and chemical additions of other boron compounds decreased those values. While there were no significant decreases in internal bond values, the chemical addition of boric acid and borax decahydrate to urea-formaldehyde resin increased the internal bond values of MDF boards. It was observed that in both types of addition, borax pentahydrate reduced the formaldehyde emission values of MDF boards the most and also reduced the burnt area by up to 30%. When the type of addition of boron compounds to urea-formaldehyde was compared, the addition of boron compounds at the resin formation stage showed better results in the properties of MDF boards than physical addition.